Development of a virtual bench for the analysis of the physical processes of internal combustion engines (2021)
Currently, internal combustion engines face the challenge of reducing fuel consumption and reducing polluting emissions due to their significant impact on the environment. Therefore, it is necessary to use tools that allow us to evaluate the operating characteristics of this type of thermal machines. In the present investigation, the development of a virtual bench was proposed for the analysis of the behavior and performance characteristics of an internal combustion engine for use as a learning tool in higher education students. From the results obtained, it could be demonstrated that the pressure curves of the combustion chamber and the rate of heat release obtained by means of the virtual bench presented a high concordance with the experimental records. The maximum deviation obtained was 5% and 15% for the pressure curve and the heat release rate. Comparing the performance parameters of the brake specific fuel consumption of the engine and energy efficiency, a maximum deviation of 2.96% was shown compared to the real engine. In general, the virtual development bank can describe the behavior of the engine, allowing the characterization of physical phenomena, as well as evaluating the effect of auxiliary technologies such as turbo-compression systems.